Optimization of Renewable Energy Sources in the Development of a Military Microgrid at Indonesia Defense University - Yanif Dwi Kuntjoro; Achmad Abdurrazzaq; Dwi Rahayuningtiyas; Arif Zidan Prayogo; Faris Alaudin Salih; Fulkan Kafilah Al Husein (The Republic of Indonesia Defense University, 2023)
The availability of electricity is crucial for the smooth operation and administration of any institution, including the Republic of Indonesia Defense University. This study aims to investigate the implementation of the Military Microgrid, an innovative concept developed to increase the development of renewable energy sources for defense agencies. The researchers employed a qualitative approach, conducting interviews and gathering data from various sources, including relevant laws and regulations. Implementing the Military Microgrid system at the Indonesia Defense University presents a practical and sustainable solution to meet the university's electricity demands while promoting environmental sustainability. The initiative aligns with the Indonesian government's renewable energy goals and can serve as a promising solution for other institutions to follow. This concept has facilitated the exploration of environmentally friendly energy sources from nature, such as solar, water, waste, and biomass. The Military Microgrid is an effective solution to meet the demand for electricity in defense agencies while promoting the use of renewable energy sources. The implementation of Law No. 23 of 2019 concerning the Management of National Defense Resources has provided a legal framework for developing and implementing this innovative concept. This study highlights the importance of exploring and utilizing renewable energy sources to meet the growing demand for electricity in institutions especially military and defense institutions.